2013
DOI: 10.1007/s11095-013-0998-3
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Synthesis of PEG- and Folate-Conjugated Liposomes for One-Step Formation of Targeted Stealth Nanocarriers

Abstract: Purpose A microfluidic hydrodynamic flow focusing technique enabling the formation of small and nearly monodisperse liposomes is investigated for continuous-flow synthesis of poly(ethylene glycol) (PEG)-modified and PEG-folate-functionalized liposomes for targeted drug delivery. Methods Controlled laminar flow in thermoplastic microfluidic devices facilitated liposome self-assembly from initial lipid compositions including lipid/cholesterol mixtures containing PEG-lipid and folate-PEG-lipid conjugates. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…In this method, folate conjugated phospholipid are passed through thermoplastic microfluidic device in a controlled laminar flow. This method can produce immunoliposomes in nano size range (90).…”
Section: Immunoliposomesmentioning
confidence: 99%
“…In this method, folate conjugated phospholipid are passed through thermoplastic microfluidic device in a controlled laminar flow. This method can produce immunoliposomes in nano size range (90).…”
Section: Immunoliposomesmentioning
confidence: 99%
“…Subsequently, these lipid discs bend to reduce the exposure of the hydrophobic lipid chain to the hydrophilic buffer and finally close into spherical liposomes [11]. This single-step method offers better control over the properties of liposomes, such as particle size, size distribution and surface properties (PEGylation and targeting ligand) [11][12][13][14]. More importantly, this method can be easily scaled up.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we found that TUNEL experiments showed apoptotic death of SW480 cells was also consistently increased. PEG-liposomal L-OHP degraded in cells after pinocytosis; furthermore, the intracellular drug release enhanced active drug level within cells and slowed down drug efflux, therefore, liposome entrapment of chemotherapeutics represents its dual effect on tumor cells (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%